Translation and validation of the Affiliate Stigma Scale (ASS) from English into Malay language for parents caring for their child with autism spectrum disorder (ASD) - Noor Shuhada Salleh; Yee Cheng Kueh; Maruzairi Husain; Maria Brenner (Malaysian Journal of Paediatrics and Child Health, 2026)
Objective: In the case of a child with autism spectrum disorder (ASD), stigma not only affects diagnosed children but also extends to individuals associated with them, known as affiliate stigma. The necessity for a linguistically and culturally appropriate measure of affiliate stigma among parents of a child with ASD in Malaysia is evident. This study aims to translate and validate the Affiliate Stigma Scale (ASS) from English into Malay language. Methods: The translation, back-translation, and validation process was based on the agreement of experts serving on the review committee. Content validity was evaluated by the content validity index (CVI) and a modified Cohen’s kappa index. Face validity was quantified through the input of four parents who examined the instrument. In the psychometric testing phase, utilising survey data, we implemented a pilot study with a cross-sectional research design involving 30 parents of a child with ASD. Internal consistency was evaluated using Cronbach’s alpha. Results: All items in the ASS received an I-CVI score exceeding 0.78, indicating excellent validity in terms of relevance, clarity, simplicity and non-ambiguity. The S-CVI for ASS reported acceptable content validity with a range of S-CVI/Ave from 0.986 to 1.00. The face validity was deemed good, with no major comments provided. The Cronbach’s alpha for the ASS was 0.870. Conclusions: The translated Malay version of ASS exhibited good content and face validity, reasonable levels of internal consistency and is ready to be used with Malay speakers.